Case Report: A Re-Positive Case of SARS-CoV-2 Associated With Glaucoma - Zhou, Xiaoli; Zhou, Ya-Na; Ali, Ashaq; Liang, Cuiqin; Ye, Zhiqin; Chen, Xiaomin; Zhang, Qing; Deng, Lihua; Sun, Xinyi; Zhang, Qian; Luo, Jihong; Li, Wei; et al. (Frontiers in Immunology, 2021)
The current pandemic of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has already become a global threat to the human population. Infection with SARS-CoV-2 leads to a wide spectrum of clinical manifestations. Ocular abnormalities have been reported in association with COVID-19, without specifying the nature of the impairments. Here, we report a case of a female patient diagnosed with glaucoma on re-hospitalization for ocular complications two months later, while discharged from the hospital on recovery from COVID-19. Meanwhile, the patient was found re-positive for SARS-CoV-2 in the upper respiratory tract, and the infection was also diagnosed in the aqueous humor through immune-staining by antibody against N protein and S protein of SARS-CoV-2. Considering the eye as immune privileged site, we speculate that SARS-CoV-2 survived in immune privileged sites in the eye and caused re-positive of SARS-CoV-2.